Intraoperative Nerve Mapping and Visualization System: Optimal Neurological Function Preservation in Schwannoma Surgery - Wenjianlong Zhou; Xiaoyi Shi; Qin Xu; Xiangxiang Liu; Junshi Li; Hui Qiao; Lirui Yang; Baowang Li; Liangpeng Chen; Yuan Zhang; Xiudong Guan; Shunchang Ma; et al. (SmartMat)
ABSTRACT Schwannoma surgeries pose a significant risk of postoperative neurological impairment. While intraoperative neuromonitoring (IONM) has improved surgical outcomes, it offers an indirect assessment of neural structures and functions. However, during the surgeries, it is not feasible to achieve comprehensive visualization of the nerves. To address this limitation, we introduced a multi‐channel flexible microelectrode array (FMEA) characterized by its exceptional resolution, consistent conductivity, and unwavering electrical properties. FMEA conforms precisely to the uneven tumor surface during IONM, capturing detailed spatiotemporal patterns of neural signals. Consequently, neurosurgeons can delineate nerve trajectories on the schwannoma surface with heightened precision and evaluate the functional potential of the residual nerve by analyzing signal amplitudes. For surgical guidance, we developed algorithms enabling real‐time intraoperative neuro‐mapping. This innovation is poised to refine schwannoma surgical practices, promoting nerve anatomical preservation after surgery and guaranteeing postoperative neural outcomes.